2012
DOI: 10.1111/j.1600-0684.2012.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of spontaneous air sacculitis in 37 baboons and seven chimpanzees and a brief review of the literature

Abstract: Background Air sacculitis is an important clinical condition in non-human primates. Methods We evaluated 37 baboons and 7 chimpanzees with spontaneous air sacculitis submitted to pathology over a 20 year period. Results Air sacculitis was observed almost exclusively in males. Common reported signs were halitosis, coughing, nasal discharges, depression, anorexia, and weight loss. Gross lesions included thickened air sacs and suppurative exudate lining the walls. Microscopic lesions included marked epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 8 publications
(16 reference statements)
2
41
0
Order By: Relevance
“…Apart from colonization, it was reported that transmitted S. aureus has led to severe and even lethal infection of one gorilla in the Gabonese center [3] highlighting the threat of this “humanosis” in apes. It has been reported that S. aureus can cause sepsis, skin and soft tissue infection, visceral abscess, air sacculitis and meningitis in monkeys and apes [35]. …”
Section: Introductionmentioning
confidence: 99%
“…Apart from colonization, it was reported that transmitted S. aureus has led to severe and even lethal infection of one gorilla in the Gabonese center [3] highlighting the threat of this “humanosis” in apes. It has been reported that S. aureus can cause sepsis, skin and soft tissue infection, visceral abscess, air sacculitis and meningitis in monkeys and apes [35]. …”
Section: Introductionmentioning
confidence: 99%
“…Chimpanzees had firm, inflated, red-purple lung lobes with yellow-white foci throughout the parenchyma (Schmidt and Butler, 1971). Baboons had thickened air sacs with suppurative to fibrinosuppurative exudate (Kumar et al, 2012).…”
Section: B Klebsiella Pneumoniaementioning
confidence: 99%
“…Given that air sacs can become infected (airsacculitis) (Lawson et al, 2006;Kumar et al, 2012), potentially causing disease and reducing fitness, it is argued that air sacs cannot be functionless, and that they would almost certainly be selected against unless they serve a current biological function (de Boer, 2012). Several hypotheses have been proposed regarding the function of laryngeal air sacs, including acting as visual signals, allowing the rebreathing of air to aid respiration, and aiding brachiation by stiffening the thorax (Negus, 1949;Starck and Schneider, 1960;Harrison, 1995).…”
Section: The Loss Of Laryngeal Air Sacs During Hominin Evolution: Evimentioning
confidence: 99%